She kills me : the true stories of history's deadliest women - Wright, Jennifer, 1986- (Abrams Image, 2021)
"A powerful collection of stories about women who murdered--for revenge, for love, and even for pleasure--rife with historical details that will have any true crime junkie on the edge of their seat"--Amazon.com.